2015
DOI: 10.1155/2015/161720
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective, Antioxidant, and Anticancer Effects of theTragopogon porrifoliusMethanolic Extract

Abstract: Tragopogon porrifolius (Asteraceae), commonly referred to as white salsify, is an edible herb used in Lebanese folk medicine to treat cancer and liver dysfunction. In this study, we investigated the antioxidant activity of Tragopogon porrifolius methanolic extract, both in vitro and in vivo, in addition to its hepatoprotective and anticancer activities. Total phenolic and flavonoid contents were measured and found to be 37.0 ± 1.40 mg GAE/g and 16.6 ± 0.42 mg QE/g dry weight, respectively. In vitro antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
2
7
1
Order By: Relevance
“…The results showed that Tragopogon porrifolius plant investigated in this study are richer with phenolic compounds (87.3 to 145.3 mg/g) than that from Turkey (from 63.4 to 68.9 mg/g caffeic acid) [4] or from Lebanon (37.0 mgGAE/g) [1]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that Tragopogon porrifolius plant investigated in this study are richer with phenolic compounds (87.3 to 145.3 mg/g) than that from Turkey (from 63.4 to 68.9 mg/g caffeic acid) [4] or from Lebanon (37.0 mgGAE/g) [1]. …”
Section: Resultsmentioning
confidence: 99%
“…It was interesting to compare TFC of Tragopogon porrifolius plant analyzed in this study (range: 4.8–28.5 mg/g) with that from other countries (4 to 210 mg/g quercetin for Tragopogon porrifolius from Turkey [4] and 16.6 mg/g quercetin for Tragopogon porrifolius from Lebanon [1]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations